Química e cidadania: uma abordagem a partir do desenvolvimento de atividades experimentais investigativas - Oliveira, Ricardo Castro de (Universidade Federal de São Carlos, 2009)
The goal of this study was to investigate the contribution of investigative experimental activities in the development of decision-making process and students´ citizen formation. The data collection was made during a short course of 40 hours with high school first year students of a public school at São Carlos city, São Paulo state. The subject fuel was discussed and the investigative experimental activities were related to gasoline, ethanol and biodiesel. Before the accomplishment of these activities, the researcher promoted discussions about education perspective in Science-Technology-Society (STS). Aiming the data analysis, it was requested to students write their procedure proposition to each activity. In addition, the researcher filmed the class and took notes. Based on the analysis of results, it was possible to verify that the use of experimental activities through the investigative approach coupled with the discussions helped the students in the decision-making process about socio-scientific controversies situations, which is essential in the development of citizenship. Moreover, these activities contributed in various aspects of the students formation, such as the development of conceptual, procedural and attitudinal skills, giving to students more accurate view of science, in other words, a view of science as a human activity in permanent construction.
Keywords: Química - estudo e ensino; Experimentação; Cidadania; Atividades experimentais investigativas; Chemistry teaching; Investigative experimental activities; Citizenship; CIENCIAS HUMANAS::EDUCACAO